'Crossing the line': Criminological expertise, policy advice and the 'quarrelling society'. (August 2015) - Drake, Deborah H.; Walters, Reece
In October 2009, Professor David Nutt, eminent neuropsychopharmacologist and world leading expert on drugs, was dismissed as Chair of the UK government's Advisory Council on the Misuse of Drugs for comments he made at the Centre for Crime and Justice Studies' Eve Saville lecture. This article considers the role of evidence in political decision-making through the case of David Nutt. It is argued that the status of expert knowledge is in crisis for both the natural and the social sciences. We examine the role of the criminological advisor within emerging discourses of public criminology and suggest that high-stakes political issues can open up unprecedented opportunities for critical voices to engage in unbridled critique and to mobilise movements of dissent.